With and for the students - Voon, Boo Ho (Universiti Teknologi MARA, Sarawak, 2017)
A prime lecture entitled ‘Out of the Vicious Cycle’ by Tan Sri Datuk Amar (Dr.) Hamid Bugo, the President of MASA was held on 10 April 2017) at UiTM Sarawak, Samarahan Campus. It was attended by more than 250 participants including lecturers, board members of MASA (the Institute of Management Sarawak) and bachelor degree students. The event was organized by Service Research Group (ServGroup) in collaboration with the MASA Student Chapter (UiTM Cawangan Sarawak). The Campus Rector, Professor Dato Dr. Jamil Haji Hamali officiated the event which was also attended by Associate Professor Dr. Voon Boo Ho (Head for Service Research Group & Advisor for MASA Student Chapter), ServGroup cum organizing committee members (Dr. Kuldip Singh, Patricia Melvin Jussem, Vloreen Nity Mathew, Ardiana Mazwa Rauda Amir Abdullah), and the President for MASA Student Chapter with all his organizing committee members.